Setting the Stage: Statistical Collaboration Videos for Training the Next Generation of Applied Statisticians. Issue 2 (6th August 2021) - Sharp, Julia L.; Griffith, Emily H.; Higgs, Megan D.
Abstract: Collaborative work is inherent to being a statistician or data scientist, yet opportunities for training and exposure to real-world scenarios are often only a small part of a student's academic program. Resources to facilitate effective and meaningful instruction in communication and collaboration are limited, particularly when compared to the abundant resources available to support traditional statistical training in theory and methods. Our work helps fill the need for resources by providing ten modern, freely-available videos of mock collaborative interactions, with supporting discussion questions, scripts, and other resources. Videos are particularly helpful for teaching communication dynamics. These videos are set in the context of academic research discussions, though the scenarios are broad enough to facilitate discussions for other collaborative contexts as well. The videos and associated resources are designed to be incorporated into existing curricula related to collaboration. The materials have been piloted with positive feedback from students and instructors. Supplemental files for this article are available online.